A phase 2 study of fosaprepitant combined with high-dose dexamethasone for Japanese cancer patients receiving highly emetogenic chemotherapy. Issue 25 (June 2018) - Kumagai, Hozumi; Kusaba, Hitoshi; Yamanaka, Takeharu; Nio, Kenta; Inadomi, Kyoko; Takayoshi, Kotoe; Ito, Mamoru; Tamura, Shingo; Makiyama, Akitaka; Makiyama, Chinatsu; Hirano, Gen; Shibata, Yoshihiro; et al.
Abstract: Purpose: Combination therapy of fosaprepitant, dexamethasone (DEX) and a serotonin (5-HT3 ) receptor antagonist is a standard antiemetic prophylaxis for patients receiving highly emetogenic chemotherapy (HEC). However, the appropriate dose of DEX has not been established in Japan. This study determined the efficacy and safety of triplet antiemetic prophylaxis in Japanese patients receiving HEC when administered the same doses of DEX as those given in a previous international phase 3 study on this drug. Methods: To assess the efficacy and safety of a sufficient dose of DEX (12 mg on day 1, 8 mg on day 2, 16 mg on days 3 and 4) in combination with intravenous fosaprepitant and granisetron, we prospectively examined patients receiving HEC including cisplatin (≥50 mg/m 2 ). The primary endpoint was to determine the percentage of patients who had achieved a complete response (CR), which was defined as no vomiting and no rescue therapy during the entire treatment course. Results: Between February 2013 and January 2015, 44 patients were enrolled with a median age of 65 years (range, 30–75). There were 34 males (77.3%) in the study. Most of the patients had upper gastrointestinal cancers. The CR rate during the treatment course was 70% (95% confidence interval [CI]: 55%–83%) in the overall phase and 91% (95% CI: 78%–97%) in the acute phase and 70% (95% CI: 55%–83%) in the delayed phase. Appreciable severe toxicities related to the antiemetic therapy were not observed. Conclusions: These results suggest that a sufficient dose of DEX in combination with fosaprepitant and granisetron is optimal as an antiemetic prophylaxis for Japanese patients receiving HEC.